(untitled) (Latakia University Journal -Basic Sciences Series, 2016)
A new selective PVC (poly vinyl chloride) membrane electrode for Copper(II) ion was prepared depending on a complex of 1,3-diphenyl-5-(P-nitrophenyl) formazan (FM) as ionophore with copper(II). The best performance was obtained by a membrane electrode with the composition: PVC as matrix (32 %), (FM) as ionophore (3 %), DBP (Dibutyl phthalate) as plasticizer (64%), and NaTBP (Sodium tetraphenylborate) as anionic additive (1%). This electrode exhibited a linear potential response to copper(II) in the concentration range 1.0 × 10−6 – 1.0 × 10-1 M with Nernstian slope of 28.23 mV/decade and detection limit down to 7 × 10−7 M, a response time of about 15 secs, and a life time which exceeded two months over a wide range of PH:3-6. The suggested PVC electrode had a high selectivity for copper over a large number of alkaline and alkaline earth ions and some heavy metals ions. Described membrane electrode could be successfully used in analytical measurements by direct potentiometry for the determination of Cu+2 in standard and real sample solutions. تم في هذا البحث تحضير الكترود غشاء بولي ﭬنيل كلوريد (PVC ) جديد انتقائي لأيون النحاس+ Cu2 بالاعتماد على معقد النحاس (II) مع 1 – 3- ثنائي فنيل – 5 –(- p نترو فنيل) فورمازان كمادة فعالة كهركيميائيا , وتبين من خلال الدراسة أن الغشاء ذو التركيب (32%) PVC , 3% مادة فعالة كهركيميائيا , 64% مادة ملدنة DBP (ثنائي بوتيل فتالات), 1% NaTPB (صوديوم رباعي فنيل بورات) كإضافة هو الافضل, حيث يبدي استجابه جهدية (نيرنيستية) خطية تجاه أيون النحاسCu2+ ضمن مجال خطي واسع( 1.0 × 10-1 - 1.0 × 10-6) مول/لتر وميل28.23 mv/decade بحد كشف بحدود 7×10-7 M و زمن استجابة بحدود 15 sec. وزمن حياة طويل يتجاوز الشهرين , كذلك ضمن مجال واسع pH بين 6 – 3 , وتبين من خلال حساب معاملات الانتقائية باستخدام طريقة الكمون الموافق Matched Potential Method(MPM), إن الكترود غشاء PVC المقترح يتمتع بانتقائية عالية لأيونات Cu+2 بوجود العديد من الايونات القلوية والقلوية الترابية وبعض أيونات المعادن الثقيلة الأخرى, واستخدم الالكترود المقترح بنجاح في تحديد تركيز النحاس +Cu2 في عينات قياسية وأخرى واقعية من البيئة المائية . الكلمات المفتاحية : ايون النحاس (II) , ISE , أصبغة الفورمازان , الكترود غشاء PVC ,المعايرة الكمونية.